Kritik Objektifikasi Perempuan pada Lirik Lagu Nxde karya (G)-IDLE - Nabila Hamidah Ath Thahirah; Alex Sobur (UNISBA Press, 2024)
Abstract. The research entitled “Criticism of the Objectification of Women in the Song Lyrics Riffaterre's Semiotic (Analysis of the Lyrics of the Song Nxde by (G)-IDLE) was motivated by the public's interest in this song so that it went viral on various social media because the message contained social criticism, especially the objectification of women in the lyrics. Song lyrics can be used as a forum for sharing knowledge and views about social issues that affect a community or nation, as well as entertainment. This research aims to find out how the meaning is contained, especially regarding criticism of the objectification of women in the lyrics of the song Nxde through Riffaterre's semiotic theory approach in terms of four stages, namely, heuristics and hermeneutics, matrix, model and variant, and hypogram. The research method used is qualitative descriptive research. Data collection techniques in this research are observation and documentation. The research results show that heuristic and hermeneutic reading does not only mean criticism of objectification and stereotypes of women, but also how they rise up and accept themselves as they are. The matrix of the lyrics of this song is a stereotype of women and is objectified by other people. The model for the lyrics of this song is the character